Telemedicine Follow-Up for Intravitreal Bevacizumab Injection in the Stanford University Network for Diagnosis of Retinopathy of Prematurity (SUNDROP) Cohort - Ji MH; Callaway NF; Greven MA; Vail D; Moshfeghi DM (Clinical Ophthalmology, 2020)
Marco H Ji,1 Natalia F Callaway,1 Margaret A Greven,2 Daniel Vail,1 Darius M Moshfeghi1 1Byers Eye Institute, Horngren Family Vitreoretinal Center, Department of Ophthalmology, Stanford University School of Medicine, Palo Alto, California; 2Department of Ophthalmology, Wake Forest University School of Medicine, Winston-Salem, North CarolinaCorrespondence: Darius M Moshfeghi Tel +1 (650) 723-6995Email dariusm@stanford.eduAbstract: Telemedicine has emerged as a potential solution to face the disproportion between infants that need to be screened for retinopathy of prematurity (ROP) and the lack of ophthalmologists. We evaluated its utility in the follow-up after off-label intravitreal injection of bevacizumab. None of the treated infants ended up with bad anatomic outcome. Telemedicine is an alternative safe method to monitor patients after treatment.Keywords: pediatric retina, retina, pediatric ophthalmology